CORRELATION OF DEPRESSION SYMPTOMS WITH FEMALE SEXUAL FUNCTION INDEX IN FEMALE HEMODIALYSIS PATIENTS - Bonendasari, Agni (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTIntroduction. Hemodialysis patients experience major changes in lifestyle and suffer various physical and emotional symptoms, especially symptoms of depression and sexual dysfunction in more than half of patients. Sexual dysfunction in women is often not identified because of lack of attention, especially by the clinician. Symptoms of depression limit intimacy, and affect sexual arousal and orgasm. Aim : the aim of the study was to determine the correlation between depressive symptoms and female sexual function index (FSFI) in women hemodialysis patients in the Hemodialysis Unit of Dr. Sardjito General Hospital Yogyakarta.Methods. The method of this study was cross-sectional. Research was conducted at the Hemodialysis Unit by Dr. Sardjito General Hospital Yogyakarta from 10 April to 24 April 2012. Result. There were 42 female patients undergone routine hemodialysis who met the criteria. The median age was 49 years old and had undergone hemodialysis for a median duration of 40 months. Conclusion. There was a negative correlation of depression symptoms and female sexual dysfunction with a moderate strength (r = -0.421) and statistical significantly (P <0.05). Age and prolactin had a negative correlation with a moderate strength of FSFI score. HDL levels and menstrual status had a positive correlation with FSFI, with weak and strong correlation respectively.Â Key Words: Female sexual function index, depression, hemodialysis